Experiencia profesional en el campo laboral de los graduados de la carrera de Administración Pública de la ESPAM MFL, periodo 2021-2022 - Saltos Vélez, Carelys Nayeli (2024)
The objective of this research was to evaluate the impact of professional experience in the labor field of graduates of the Public Administration career for the Period 2021-2022 to improve the professional profile. Within the methodology used, the survey technique stands out, applied to both the graduates of the degree, who provided information about their current employment situation, and an interview with representatives of public sector organizations, with the aim of identifying the most important aspects when selecting professionals according to their Professional Experience. Among the research methods used are the inductive - deductive, the analytical - synthetic and the correlation method which allow us to understand the problems of the study and its characteristics. In the results, it is observed that 66% of graduates report being currently working. Of this group, 30% in the private sector, 11% in the public sector and 41% work independently due to difficulties in finding employment. Currently, it is recognized that organizations are based on valuing the professional's professional experience, postgraduate studies and complementary training when hiring, while other elements such as knowledge of languages or technology are not such a priority. Finally, a strategy plan is proposed to help increase the job placement rate of the Public Administration Graduate.